The Study of Side Coordinateâ€™s Function and Effective Application Plan to Reduce Cyber-Sickness in Driving Simulation - Jeong, Hyo-won; Park, Sung-Soo; Sung, Jung-Hwan (International Journal of Engineering and Technology, 2018)
Background/Objectives: We focused on objects around player as another element to reduce â€œCyber-sicknessâ€, which has been treated as serious problem in VR research. Therefore, we defined these objects as â€œSide Coordinateâ€.Methods/Statistical analysis: We constructed several environments for experiment with different standards based on the cognitive speed formula to discover correlation between side coordinate and cyber-sickness. 30 subjects in their 20s participated in the experiment and we surveyed them with SSQ(Simulator sickness Questionnaire) to analyze whether they felt cyber-sickness. We also examined 3 main elements of cyber-sickness to find out which one has the greatest effect on the sickness.Findings: The results of the survey were analyzed by One-way ANOVA and â€˜Scheffeâ€™ method for the â€˜Post Hocâ€™ test in SPSS program was used for detail information. According to the results in the experiment, we found side objects caused more cyber-sickness when distance between objects and player, which is called â€œSide Distanceâ€ becomes too far. Not only side distance, but distance between objects, which is called â€œObject Distanceâ€ also caused the disorientation in the analysis of 3 components, which are nausea, oculomotor, and disorientation that constitute cyber-sickness. When side distance and object distance were set to the shortest distance, subjects felt disorientation. Especially, long side distance caused the worst disorientation problem based on statistical analysis. It can be deduced that a disturbance between visual and vestibular information occurs due to the difference between the actual speed and the cognitive speed, resulting in cyber-sickness. And we can infer that disorientation is the main factor in cyber-sickness among 3 elements.Improvements/Applications: Lastly, using cognitive speed formula to get proper distance between side objects could help VR developer match the actual speed and perceptual speed to prevent cyber-sickness.Â Â